AGE OF XENOLITH-BEARING BASALTS AND MANTLE EVOLUTION IN THE BAIKAL RIFT ZONE - Ashchepkov I.V.; Travin A.V.; Saprykin A.I.; Andre L.; Gerasimov P.A.; Khmel'nikova O.S. (My University, 2003)
Five age stages of xenolith-bearing basalts of the Vitim and Khamar-Daban lava plateaus have been recognized by K-Ar dating. Thermobarometry of the basalt melts suggests deep levels of magma derivation at the initial and final stages. The PT paths of the melt upwelling in the period of generation of lava plateau are steeper than the PT paths of hydrous lavas during the initial and final periods of volcanic activity. Temperature sections for a mineral (rock) vary quickly in time. For the Vitim Plateau, three zones of melt concentration have been expressed at Stage I (18–16 Ma): 25–27 kbar, 1300–1100 °C — deformed peridotites, kaersutite-phlogopite-bearing veins; black and hybrid pyroxenites; above 22–20 kbar — Ga- and Ga-Sp-lherzolites of primitive type and anatectic pyroxenites; 16–12 kbar — Sp-lherzolites with pargasite partings and disseminated Phl. At Stage II (14–12 Ma), magma was localized at the top of the Sp-facies among lherzolites of A-type (with enriched Al-Sp and Px). At Stage III, magma was concentrated at the bottom of the Sp-facies of the mantle: the lower part of the column — primitive lherzolites, and the upper part, A-lherzolites. Stage IV is characterized by a layered mantle: 1 — high-temperature pseudogarnet, 2 — primitive and pseudogarnet lherzolites, 3 — spinel and pseudogarnet lherzolites, 4 — mixed lherzolites of primitive depleted alumina type and low-temperature iron varieties. Stage V is represented by a 3-member section: 1 — high-temperature Fe-lherzolites, 2 — garnetspinel and spinel lherzolites, 3 — aluminous and primitive lherzolites. Peaks of Fe# at temperature sections show variations in levels of localization and concentration of magma. A similar scheme is documented for Khamar-Daban. The plume basalts whose characteristics correspond to the modal melting of primitive garnet lherzolites change their composition, remelting metasomatites and pyroxenites and coming into reaction with peridotites. Rare-earth characteristics of basalts change more quickly than the isotopic ones.
Keywords: Basalt; rift zone; melting; mantle; peridotites; pyroxenites; melt; differentiation; geochemistry; thermobarometry; inductively bound mass-plasma